Philosophy outside-in a critique of academic reason - Norris, Christopher 1947- (Edinburgh University Press, 2013)
Christopher Norris raises some basic questions about the way that analytic philosophy has been conducted over the past 25 years. In doing so, he offers an alternative to what he sees as an over-specialisation of a lot of recent academic work. Arguing that analytic philosophy has led to a narrowing of sights to the point where other approaches that might be more productive are blocked from view, he goes against the grain to claim that Continental philosophy holds the resources for a creative renewal of analytic thought